Gestão democrática e infância: o orçamento participativo criança em Santo André - Casanova, Karla Grazielle Garcia (2021)
The objective of this research is to verify the theoretical and practical aspects that contribute to the development of democratic management, focusing on the experience of the Child Participatory Budgeting Program that took place in a municipality in Greater São Paulo. To this end, the work took as its object the managerial and teaching experience during the Child-Participatory Budgeting (OP-Criança), which took place in a sector of the Education Department, which comprises two schools in the municipality of Santo André. The research universe was restricted to the examination of these experiences, in the period from 2013 to 2016. It is a qualitative research, whose methodological data collection procedures used the bibliographic research and the questionnaire carried out with three managers, who participated in the Child-Participatory Budgeting in Santo André, and four teachers from the Municipal Education Network of the city in question. The problematic of this work can be explained in the following question: “From the analysis of the Child-Participatory Budgeting experience in Santo André, what are the founding elements to promote the effective participation of children in the processes of management and pedagogical practice?”. The theoretical framework of this work is supported by the educational conception of Paulo Freire and other authors who follow the tradition of liberating pedagogies and the democratic management of education. The examination of the reality in question revealed what the Child-Participatory Budgeting contributed to the democratic formation in the municipal network of Santo André, especially with regard to the expansion of children's participation in school decisions. It showed, on the other hand, that teacher training needs to be closer to the school reality, and, at the same time, to deepen the theoretical reflections based on authors and educational concepts with a critical and democratic approach. Thus, although the Participatory Budget has not managed to solve all the main problems of schools, it can be considered an important milestone in the municipal network of Santo André, contributing to the promotion of democratic, reflective and participatory education, so that our children can become involved. make agents aware of the reading of the world and of everyday social reality.